Vegetative morphophysiological responses of four rice cultivars to drought stress - M Miftahudin; Rury Eryna Putri; Tatik Chikmawati (Society for Indonesian Biodiversity, 2020)
Abstract. Miftahudin, Putri RE, Chikmawati T. 2020. Vegetative morphophysiological responses of four rice cultivars to drought stress. Biodiversitas 21: 3727-3734. Each rice genotype develops certain morphophysiological responses to drought stress. The study aimed to analyze the morphophysiological responses of vegetative aspect of four rice cultivars to drought stress. A 10% Polyethylene glycol-6000 was added to a Yoshida nutrient solution medium as a drought stress stimulant for four rice cultivars, i.e., IR64, Hawara Bunar, Situbagendit, and Inpago 10. Fourteen-days-old rice seedlings were grown on the media with and without drought stress treatment for 9 days, and morphophysiological characters of vegetative aspects were observed. Drought stress inhibited the shoot growth of cv. Hawara Bunar, but increased shoot growth of cv. Inpago 10. The physiological responses in the form of leaf relative water content, proline, malondialdehyde (MDA), and total chlorophyll contents in cv. Hawara Bunar was inversely proportional to those of cv. IR64 showed an inferior response to drought stress. The rice cv. Hawara Bunar might develop better response mechanisms to drought than that of cv. IR64. The physiological responses of cvs. Situbagendit and Inpago 10 were in between the other two cultivars. We conclude that the variation of morphophysiological responses to drought stress among rice cultivars is an indicator of tolerance capability to drought that could be used as early-growth selection criteria in rice breeding programs for drought tolerance.